(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Jakaria, Dairoh, Setyani NMP, Sutikno, Ulum MF, Priyanto R. 2024. Determining the hybrid diversity between Bali cattle (Bos javanicus) and Wagyu cattle (Bos taurus) breeds using specific microsatellite markers. Biodiversitas 25: 3048-3055. This study aimed to determine hybrid diversity between Bali and Wagyu cattle using microsatellite markers. Total blood samples were collected from Bali purebreds (n=32 heifers), Wagyu×Bali crossbreeds, which consist of 2 bulls and 9 heifers (n=11), and Wagyu purebreds (n=6 dams). The four microsatellite markers (INRA035, ILST006, ETH225, and HEL9) were used to determine genetic diversity among cattle populations, which is part of what is recommended by FAO (Food and Agriculture Organization). GenAlex, CERVUS, MEGA10, UPGMA, and RStudio software were used for data analysis. Thirty-one alleles were identified at the four microsatellite loci used in this study. All identified alleles were polymorphic and informative. This study found 283 bp and 300 bp (ILSTS006) and 139 bp (ETH225), demonstrating the private alleles for Wagyu×Bali crossbreeds; 104 bp (INRA035), 284 bp (ILST006), 155 bp, 159 bp, and 167 bp (ETH225) were private alleles for Bali purebred, while 288 bp (ILST006), 145 bp (ETH225), and 162 bp (HEL9) were private alleles for Wagyu purebred. Based on Neighbor Joining and PCA analysis, the Wagyu purebred exhibited at the different clusters in both Wagyu×Bali crossbred and Bali purebred. These findings highlight that microsatellite markers effectively distinguished between Bali purebred, Wagyu x Bali crossbred, and Wagyu purebred cattle, providing valuable insights for breeding programs tailored to each population.